2019
DOI: 10.1177/1350650119884825
|View full text |Cite
|
Sign up to set email alerts
|

Representative volume element-based simulation of multiple solid particles erosion of a compressor blade considering temperature effect

Abstract: Solid particle erosion is one of the main failure mechanisms of a compressor blade. Thus, characterization of this damage mode is very important in life assessment of the compressor. Since experimental study of solid particle erosion needs special methods and equipment, it is necessary to develop erosion computer models. This study presents a coupled temperature–displacement finite element model to investigate damage of a compressor blade due to multiple solid particles erosion. To decrease the comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…In order to completely describe the state of stress in material, an equation of state (EOS) should be used beside the J-C model, since the J-C model just gives relations between deviatoric stresses and strains [54,56]. In the present investigation, Mie-Grüneisen EOS is used to represent the hydrodynamic component of the stress field.…”
Section: Constitutive Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to completely describe the state of stress in material, an equation of state (EOS) should be used beside the J-C model, since the J-C model just gives relations between deviatoric stresses and strains [54,56]. In the present investigation, Mie-Grüneisen EOS is used to represent the hydrodynamic component of the stress field.…”
Section: Constitutive Modelmentioning
confidence: 99%
“…Furthermore, C is defined as the intercept and S is the slope of the linear fitting of cubic shock velocity ( s u ) versus particle velocity ( p V ), as shown in Eq. ( 6) [56]:…”
Section: Constitutive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Feulner et al (2015) established a model of hail breakage in the low-pressure compressor of a turbofan engine and found that hail breakage mainly occurred during the impact on the first-stage blade. Mohammadi and Khoddami (2020) studied the effects of impact particle size, velocity and angle on the impact behavior of compressor blades under different temperature fields by simulating the impact behavior of compressor blades. Li et al (2021Li et al ( , 2023 and Bin et al (2023) designed and built a Ti-6Al-4V alloy erosion wear test bench to study the distribution area of compressor blade erosion wear.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, solid particle erosion (SPE) entails the removal of surface material due to the different sizes of solid particles entrained into the GTE that impact on and damage, for example, the compressor blades. This is a characteristic and common problem since GTEs operate across the globe in sandy environments, with an inevitable interaction between sand particles and compressor blades [2]. The sand particles usually hit the blades at high velocity and, in sufficient quantities, even relatively minute particles can induce considerable SPE damage, reducing the fatigue resistance of the blade by generating a concentration of stress at the impact site [3,4].…”
Section: Introduction 1backgroundmentioning
confidence: 99%